Reconstituting a production capability : past experience, restart criteria and suggested policies - Birkler, J. L., 1944-; Large, Joseph P.; Smith, Giles K., 1928-; Timson, F. S. (Frederick Samuel); National Defense Research Institute (U.S.). Acquisition and Support Policy Program; Rand Corporation; United States. Office of the Under Secretary of Defense, Acquisition (Santa Monica, CA : RAND, 1993)
This report evaluates the feasibility of restarting weapon system production lines in response to a resurgent major threat and suggests steps that might be taken at shutdown to ease restart. The cost and schedule advantages of restart relative to new-system production are quantified. Criteria are identified for deciding which systems ought to be regarded as candidates for restart, and the application of the criteria is illustrated. Other reconstitution options (e.g. maintaining "warm" production lines, excess production for stockpiling) are briefly reviewed.
"National Defense Research Institute."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Defense industries -- United States; Industrial mobilization -- United States; United States -- Armed Forces -- Procurement; United States -- Armed Forces -- Weapons systems